Mathematical Modelling of Typhoid Fever Transmission Dynamics and Intervention Impact in Harare, Zimbabwe (2018–2020) - Mukeredzi, Innocent; Zvoushe, Tonderai; Chonzi, Prosper; Vere, Michael; Phiri, Isaac; Birri Makota, Rutendo; Hellen Machingauta, Mandidaingeyi; Sisimayi, Chenjerai; Mapako, Tonderai; Midzi, Nicholas; Gwasira, Ethel (Journal of Model Based Research, 2025)
Background Typhoid fever remains a significant public health issue in Harare City, Zimbabwe, exacerbated by recurrent outbreaks between 2018 and 2020. Key challenges, including inadequate water supply and sanitation infrastructure, high population density, and limited healthcare access, have intensified the disease burden. Understanding the key transmission drivers and assessing the impact of various interventions are essential for informing policy and health strategies. Objectives This study aimed to: 1: To predict future trends in typhoid fever cases Harare City typhoid hot areas. 2: To develop a mathematical model to simulate the spread of typhoid fever incidence under different intervention scenarios and recommend evidence-based strategies for reducing the disease burden in Harare City. Methods A dynamic compartmental SIR-based model, adapted from the Pitzer Vaccine Effectiveness (VE) framework, was employed to simulate disease transmission. This model accounted for both short-cycle (human-to-human) and long-cycle (environmental) transmission pathways. Data from Harare City (2018–2020) were used for model calibration and forecasting, and sensitivity analysis was performed to assess the impact of different intervention levels. Findings The model identified inadequate sanitation, contaminated water sources, and low health- seeking behaviors as primary drivers of typhoid transmission. In the absence of interventions, the model projected a sustained high rate of transmission. However, treatment and WASH interventions could reduce the disease burden by 50–60%, while combined strategies incorporating vaccination and education led to an 80% reduction in cases. Sensitivity analysis indicated that treatment and WASH interventions were particularly impactful at moderate coverage levels. Conclusion Mathematical modeling effectively demonstrated the multifactorial drivers of typhoid fever transmission in Harare. Integrated interventions that combine WASH, vaccination, treatment, and education present the most promising approach for long-term control of the disease. The findings offer a solid, data-driven foundation for public health decision-making and resource allocation.
Keywords: Typhoid Fever; Mathematical Modelling; Public Health Interventions; Water; Sanitation; and Hygiene (WASH); Vaccination Coverage; Health Education